Dry Powder Extinguisher Dropper Drone - Ahmad Danyal Mustapha,; Wynnegiggs Victor,; Zahar , Mohd Muzaffar (Multidisciplinary Applied Research and Innovation, 2024)
Life, property, and the environment are all seriously at risk from fire incidents. To enhance firefighting capabilities, explorations has been done which leads to an innovative solution that have resulted in the creation of dry powder extinguisher dropper drone. These unmanned aerial vehicles (UAVs) are made with the purpose of transporting and deploying fire extinguisher balls, which are self-activating devices filled with fire suppression ingredients. This dry powder extinguisher dropper drone is fitted with sophisticated sensors that let them locate fires quickly. As soon as a fire is discovered, the drone will autonomously drop the ball containing the dry powder fire extinguisher. This drone may also enter difficult or risky environments, including high-rise structures, industrial complexes, or remote locations. These drones' main job is to scatter fire extinguisher balls. Spherical objects called "fire extinguisher balls" are used to put out fires and are packed with foam, powder, or other extinguishing ingredients. The balls are released by the drones, which activate when they encounter heat or fire, scattering the suppressant substance and dousing the flames. This device offers a quick and efficient way to put out fires, especially small and medium-sized ones. This drone has various benefits for responding to fire emergencies. They can get to the fire site quickly, cutting down on response time and lowering danger to human firefighters. Drones' aerial vantage point improves situational awareness, facilitating decision-making and resource allocation. Additionally, even in the absence of urgent human involvement, the self-activating nature of the fire extinguisher balls guarantees effective fire suppression